The early dynastic Egyptian ceramics of Kafr-Tarkhan (c. 3000-2800 B.C.) with special reference to examples in the South African Cultural History Museum, Cape Town - Boshoff, Anlen Isabella Joan (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1995.